Analisis Penyebab Emiten Delisting Serta Akibat Yang Didapatkan Para Pemegang Saham - Puteri Asyifa Octavia Apandy (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2022)
The capital market can be interpreted as a market that provides facilities for the issuance and trading of financial securities such as shares. Every issuer has a goal to move forward, but in real life some issuers end up being delisted. Based on this, this writer aims to analyze the causes of issuers being delisted and what the consequences are for shareholders. This study uses a descriptive qualitative approach. It can be concluded that the cause of the issuer being delisted is because the issuer has violated the rules, negative business conditions occur, bankruptcy, cannot generate operating income and the issuer's finances are unstable. As a result, the first shareholders can receive all the funds back, the second can receive a few percent (%) of the funds, the third will lose all their funds or the funds will not return completely, so it is advisable to be careful when choosing issuers to invest. Keywords: Delisting; Issuers; Share; Shareholders.